Evaluation of Paranormal Belief Levels of Undergraduate Students - Ulukaya Oteles, Ulku; Kocoglu, Erol; Demir, Fatima Betul (Dergipark Akad, 2024)
Paranormal beliefs are non-sensory phenomena such as astrology, superstition, and unusual life forms that cannot be explained scientifically. Although these phenomena are effective on the lifestyles of societies, they cause some societies to have outdated attitudes and behaviors. This situation makes it difficult for societies to adapt and develop to the scientific world. Paranormal beliefs come to the fore especially in shaping the lifestyles and futures of young people. It is thought that a significant part of the young population is at the undergraduate level and that the young people at this level can more consciously evaluate paranormal beliefs, which are phenomena and situations that have no equivalent in science. In this study, it was aimed to determine and evaluate the paranormal belief levels of undergraduate students. The quantitative study group of this research, which was designed with a parallel mixed method design, consists of 357 undergraduate students and the qualitative study group consists of 30 undergraduate students. Paranormal Belief Level Scale and Semi-Structured Interview Form were used as data collection tools in the research. In the analysis of the obtained quantitative data, t-test from parametric tests, ANAVO; Content analysis was used in the analysis of qualitative data. According to the results obtained from the research, it is seen that the paranormal beliefs of undergraduate students are moderate and differ in the context of various variables (gender, class level, etc.). In addition, undergraduate students stated that paranormal beliefs have various reflections on their daily lives. In line with these results, scientific education to be given to students can contribute to their critical evaluation of paranormal beliefs.
Keywords: Evaluation; Paranormal belief; Undergraduate students